HARMONISASI REGULASI KEPEMILIKAN TANAH PERTANIAN SECARA ABSENTEE BAGI PEGAWAI NEGERI DALAM PROGRAM LANDREFORM - Tristanto, Yunizar Wahyu (Legality : Jurnal Ilmiah Hukum, 2018)
Peoples needs can not be separated from the need of land . Once the importance of soil functions for society , need to be regulated in order to ensure the mastery and utilization at the same time in order to create legal certainty for the public . The problem that then arises since the start time of independence is disproportionate land ownership . In order to overcome these problems , the government has enacted Law No. 5 of 1960 About the Agrarian and the Reformation has been set TAP MPR No. IX / MPR / 2001 on Agrarian Reform and Natural Resources Management . One important aspect of the law with the enactment of the UUPA is a program of Landreform in Indonesia . Landreform became one of the alternatives for agrarian justice to resolve agrarian disputes and conflicts . one of the land reform program is the prohibition of absentee ownership of agricultural land. The problem that then occurs is the existence of exceptions in absentee land ownership . The problems regarding the permissibility of absentee ownership of agricultural land by the Servants . The exception contained in Article 3 Paragraph (4) of Government Regulation No. 224 of 1961 on the implementation of Land Distribution and Provision of Compensation. Ownership and control of agricultural soils in absentee in Article 10 Paragraph (1) UUPA is basically prohibited, but in Article 3 Paragraph (4) PP No. 224 years 1961, the government granted an exemption absentee ownership of agricultural land to some legal subjects of the Servant , retired civil servants , widows and widows of civil servants retired civil servants.